Dorsally and volarly angulated extra-articular malunions of the distal radius treated with volar corrective osteotomy and volar locking plate fixation. A case series of 19 patients with a long-term follow-up - Di Maro, Agostino; Meroni, Matteo; Stissi, Placido; Surace, Michele Francesco; Cherubino, Mario; Fagetti, Alessandro (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: To date, different technique of corrective osteotomy for the treatment of distal radius extra-articular malunions are described. With this study, we present a case series of corrective osteotomy using volar plate fixation to treat volar and dorsal extra-articular malunions aiming to evaluate the effectiveness of corrective osteotomies through volar plate stabilization in these two types of extra-articular malunions.Methods: Between August 2008 and May 2017 all patients diagnosed with extra-articular malunion were included in the study. An extended volar Orbay approach and two types of dedicated volar locking plate (Medartis AG, Switzerland and Acumed, Hillsboro,OR) were used. Clinical and radiological parameters were evaluated. The DASH and PRWE scores and the VAS scale questionnaires were administered. The results were analyzed through statistical evaluations.Results: A retrospective analysis of 19 patients diagnosed with extra-articular malunion was carried out. Nine had a volar type deformity (group A), while the other 10 had a dorsal type deformity (group B). The active range of motion (aROM), radiographic parameters, grip strength and pinches in both groups were statistically improved, except for radial deviation in both groups, ulnar deviation in group A, and radial inclination in group B.  The grip strength and pinches values were slightly better in group A. DASH, PRWE scores and VAS scale showed a significant improvement.Conclusion: Corrective osteotomy through volar fixation is an effective technique to treat both extra-articular dorsally and volarly angulated malunions. Statistically significant benefits are present in both types of deformities, with better outcomes in the group of volar deformities.